Peningkatan Lapisan Pemahaman Konsep Luas Bangun Datar Mahasiswa melalui Model Pembelajaran PRAKTAK - Viktor Sagala; Ahmad Hatip (Universitas Syiah Kuala, 2018)
The objective of this study was to describe the increase in the prospective student teachers conceptual understanding of the area of plane geometry by applying the practicum-axiomatic learning model (PRAKTAK). The PRAKTAK learning model is a combination of practicum and axiomatic methods in learning of proving the area of plane geometry. The evaluation was carried out using a modified Pirie-Kieren model of the layers of concept understanding hypothesized in 1994 and developed by cognitive psychology experts from 2002 to 2017. The research subjects were third-semester students of the Mathematics Study Program at FKIP Unitomo Surabaya. A set of questions is administered to the subjects after participating in learning using the PRAKTAK model, followed by an interview. The data of worksheets and interview transcripts were analyzed qualitatively. The results showed that before the implementation of PRAKTAK learning model, the understanding layer of subjects satisfied the first to fourth layers, namely primitive knowing, image making, having images and property noticing. After the implementation of PRAKTAK learning model, the understanding layer of the subjects increased, fulfilling the fifth and half of the sixth layer, namely formalizing and observing. Thus, the subjects met the semi observing layer. The PRAKTAK model can be applied in a geometry learning, and the modified Pirie-Kieren understanding model can be employed as an alternative evaluation tool.